Happy New Year and Thank You! - Pond, Gina A., Rev. (Open Source Alexandrian and Witches’ Order of the Golden Dawn Collections, 2014)
Rev. Gina Pond provides a short Thank You All for making the first 6 months of This Week In Heresy a success! https://www.youtube.com/watch?v=KAJH4Zxdbv0&feature=youtu.be
The Heretic Speaks episode 11, December 29, 2014
heretic-speaks_ep11_20141231.mp3 | MP3 Format Sound | 00:05:28 | 5.02 MB | 12/8/2018 10:34:16 AM | .mp3
Keywords: Pond, Gina, 1976---Sermons; This week in heresy (Podcast); Podcasts